Teacher Education in EMI: Effective Practices, Challenges, and Needs (Papeles, 2026)
Introduction: Teacher training in EMI may pose certain challenges in countries where rates of English language proficiency are not high. This study examined the perspective of pre-service English teachers and teacher educators on effective English as a Medium of Instruction (EMI) teaching practices, the challenges involved, and the immediate needs of teacher education in Ecuador. Methodology: In this mixed-method study, the researcher collected data from 123 pre-service teachers through a quantitative survey on their preferred teaching practices and conducted in-depth interviews with five teacher educators at a teacher training university to explore challenges, needs, and best practices, as well as to identify points of alignment and areas requiring adaptation. Results and discussion: The findings indicate that both groups of participants value lecturing and Active Learning (AL) strategies in EMI teacher training. Specifically, lectures are valued for their time efficiency and for simplifying complex concepts for all participants, and AL is praised for fostering engagement, critical thinking, and knowledge application. However, implementing these practices is not without challenges, as lectures pose challenges to student engagement and knowledge retention, and AL is criticized for uneven participation, time inefficiency, student fatigue, and limitations in addressing complex subjects. Moreover, suitable EMI teaching materials that align with learners’ proficiency levels are scarce. Conclusions: Effective teaching practices to respond to the challenges identified in this study involve combining lectures and active learning to minimize the obstacles and maximize the benefits of each method of instruction. Immediate needs include developing suitable materials that are easy to read and integrating active learning techniques with traditional lectures.